EMBEDDING ICT IN THE TEACHING OF WRITING: WEBLOG AS AN ALTERNATIVE TOOL - Dian Asa Utari (Universitas Pesantren Tinggi Darul Ulum Jombang, 2012)
Dian Asa Utari Muhammadiyah University of Sidoarjo dian_asa_demos@yahoo.com Abstract The arrival of digital technology has done much to change the way in which learning is displayed, shared, and analyzed in multimedia, as well as hypermedia environments. The adoption level of emerging web technologies is on the rise in academic settings. Students become more technologically literate and the trends of writing are shifting from paper-based texts to screen based texts. This paper first points out the teaching of writing in the digital age, with the integration of Information and Communication Technologies where Weblog is used as a promising tool. Toward this end, this paper further explains briefly about Weblog in writing course, its features and types, and technical matters concerning how to use weblog for writing instruction. The advantages of using Weblog are also described in this paper, carrying out the idea of utilizing Weblog in the writing subjects in the higher level of education. Key words: information and communication technologies, weblog, teaching of writing Abstract Kedatangan teknologi digital telah banyak mengubah cara pembelajaran dimana pembelajaran ditampilkan, dibagi, dan dianalisis dalam multimedia, demikian juga lingkungan hypermedia. Tingkat adopsi teknologi web meningkat di setting akademik. Siswa menjadi lebih melek teknologi dan tren penulisan beralih dari berbasis kertas naskah berbasis layar teks. Makalah ini pertama menunjukkan pengajaran menulis di era digital, dengan integrasi Teknologi Informasi dan Komunikasi di mana Weblog digunakan sebagai alat yang menjanjikan. Sampai disini, tulisan ini lebih lanjut menjelaskan secara singkat tentang Weblog dalam mata kuliah writing, fitur dan jenis-jenisnya, dan hal teknis mengenai bagaimana menggunakan weblog dalam pengajaran writing. Keuntungan menggunakan Weblog juga dijelaskan dalam makalah ini, melaksanakan ide memanfaatkan Weblog dalam mata kuliah writing di level universitas. Kata kunci: information and communication technologies, weblog, teaching of writing